Syzygium cumini (L.) skeels: a prominent source of bioactive molecules against cardiometabolic diseases - Chagas, Vinicyus Teles; França, Lucas Martins; Malik, Sonia; Paes, Antonio Marcus de Andrade (Frontiers in Pharmacology, 2015)
Syzygium cumini (Myrtaceae) is a worldwide medicinal plant traditionally used in herbal medicines due to its vaunted properties against cardiometabolic disorders, which include: antihyperglycemic, hypolipemiant, antiinflammatory, cardioprotective and antioxidant activities. These properties have been attributed to the presence of bioactive compounds such as phenols, flavonoids and tannins in different parts of the plant, albeit the knowledge on their mechanisms of action is scarce. This mini-review highlights the cardiometabolic properties of S. cumini by correlating its already identified phytochemicals with their described mechanisms of action. Data herein compiled show that some compounds target multiple metabolic pathways; thereby, becoming potential pharmacological tools. Moreover, the lack of clinical trials on S. cumini usage makes it a fruitful field of interest for both scientific community and pharmaceutical industry.